Cute, cuddly and completely crushable: Plushies as avatars in video games. Issue 2 (1st June 2021) - Reay, Emma
This article examines video game avatars that are designed to resemble toys. It names this trope the 'Blithe Child' to capture the carefree, careless and childlike interactions this avatar invites. This article argues that the connection between the Blithe Child and traditional toys functions to express and explain non-violent game mechanics, to shape sentimental player‐avatar relationships, to create cosy, snug playspaces and to encourage pro-social, creative and self-expressive playstyles. However, the Blithe Child inherits some of the more sinister dynamics latent in human‐toy relationships, namely the desire to humiliate and mutilate the cute object and anxieties about what it means to be 'real' ‐ to be an independent, agential subject rather than a passive, manipulated, othered object. Drawing on theories derived from cuteness studies and toy studies, this article uses a close reading approach to critique the age-based hierarchies that underpin this trope.